2014
DOI: 10.1007/978-1-4939-0992-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Genome Modification via Triple Helix Formation

Abstract: Triplex-forming oligonucleotides (TFOs) are capable of coordinating genome modification in a targeted, site-specific manner, causing mutagenesis or even coordinating homologous recombination events. Here, we describe the use of TFOs such as peptide nucleic acids for targeted genome modification. We discuss this method and its applications and describe protocols for TFO design, delivery, and evaluation of activity in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…PNAs are capable of binding with cognate DNA either along the major groove of dsDNA by Hoogsteen-base pairing at homopurine/pyrimidine stretches or binding directly by Watson-Crick base pairing after DNA duplex strand invasion [ 4 ]. Triplex formation creates an altered helical structure that is recognized by endogenous DNA repair factors that can induce recombination of a single-stranded donor DNA encoding a desired modification at a nearby genomic location ( Figure 1 ) [ 8 , 9 , 10 , 11 ]. The ability of PNAs to induce recombination comes directly from their ability to tightly bind at their cognate sites, as they do not possess any direct nuclease activity, a feature that greatly increases the safety profile of PNAs.…”
Section: Introductionmentioning
confidence: 99%
“…PNAs are capable of binding with cognate DNA either along the major groove of dsDNA by Hoogsteen-base pairing at homopurine/pyrimidine stretches or binding directly by Watson-Crick base pairing after DNA duplex strand invasion [ 4 ]. Triplex formation creates an altered helical structure that is recognized by endogenous DNA repair factors that can induce recombination of a single-stranded donor DNA encoding a desired modification at a nearby genomic location ( Figure 1 ) [ 8 , 9 , 10 , 11 ]. The ability of PNAs to induce recombination comes directly from their ability to tightly bind at their cognate sites, as they do not possess any direct nuclease activity, a feature that greatly increases the safety profile of PNAs.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in the late 1980s that triplex-forming oligonucleotides (TFOs) could bind to the major groove of duplex DNA to form stable triple helical structures, 23 and that they are capable of carrying out site-specific modification of chromosomal DNA. 24,25 In the liver, TFOs have been successfully used to downregulate the expression of α1-collagen and improve liver fibrosis; [26][27][28][29] and to induce cell death and regression of diethylnitrosamine-induced liver tumors in rats and HepG2 cells by targeting c-Met. 30 These reports demonstrated that TFO-mediated genomic modification might have therapeutic potential for LTGT applications.…”
Section: Triplex-forming Oligonucleotidesmentioning
confidence: 99%
“…The initial approach to the triple‐helix site‐directed modification of DNA used crosslinking agents, such as psoralen or other mutagens covalently attached to the triplex‐forming oligonucleotide . This technique has been shown to modify episomal DNA in mammalian cells in vitro and to create targeted gene knockouts of the genomic hypoxanthine phosphoribosyltransferase gene in cultured cells .…”
Section: Targeted Gene Editingmentioning
confidence: 99%
“…Triplex DNA leverages the formation of a 3-stranded or triple-helical nucleic acid structure to perform sitespecific modification of genomic DNA. 135 Essentially, the exogenous third strand of nucleic acid binds in the major groove of a homopurine region of the DNA and forms Hoogsteen or reverse Hoogsteen hydrogen bonds with the purine base. 136 The triplex formation can occur at the physiologic pH, but the polypurine regions must be guanine-rich and 12 to 14 nucleotides in length for adequate triplex formation to occur.…”
Section: Triplex Dnamentioning
confidence: 99%
See 1 more Smart Citation